Screening musicality in children: Development and initial validation of a new tool for rapid assessment of musical profiles - Verena Buren; Daniel Müllensiefen; Franziska Degé (PLoS ONE, 2025)
Musical development in childhood follows universal trajectories, such as the acquisition of basic rhythm and pitch recognition, alongside individual differences shaped by environmental, educational, and innate factors. Despite the importance of understanding these aspects for both research and educational purposes, there remains a significant gap in the availability of validated tools that can quickly and comprehensively assess musicality in children. To address this gap, this paper presents a series of studies on the development and validation of the Child Musicality Screening, a standardised instrument for the assessment of musicality in children aged 3 to 10 years. In Study 1, an initial pool of items was compiled and administered to 810 adults (293 English-speaking, 517 German-speaking) who regularly interact with children. Factor analysis was used to reduce the number of items and to identify three key dimensions of child musicality: Enthusiasm and Motivation, Music Perception, and Music Production. In Study 2, confirmatory factor analysis on ratings of parents (n =  305) and educators (n =  250) indicated moderate to high model fit, confirming the factor structure of the questionnaire. Interrater agreement between parents and educators was significant, with moderate agreement on the total scale and subscales. Preliminary evidence of convergent and divergent validity was also obtained. Study 3 further established the convergent and divergent validity, as well as internal reliability and test-retest reliability, of the instrument, using both English (n =  323) and German (n =  384) samples. Overall, the Child Musicality Screening is a newly developed tool for assessing individual musical profiles in children aged 3 to 10 years, with initial evidence supporting its validity and reliability. Available in both English and German, it offers a promising approach for researchers and educators to assess musicality, map developmental trajectories, identify musically gifted children, and enhance targeted music education.